Continuous stochastic detection of amino acid enantiomers with a protein nanopore. - Boersma, A; Bayley, J (2012)
A stochastic sensing method: Discrimination between enantiomeric amino acids is achieved when the amino acids bind to a CuII complex within a protein nanopore sensor, which provides a chiral environment. The potential of the method is demonstrated by real-time observation of the increase in enantiomeric excess during an enzymatic kinetic resolution. Copyright © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.